SLAP Tears - Steven B. Cohen MD; John R. Matthews MD (SAGE Publishing, 2021)
Background: Superior labral tears are frequently encountered during shoulder arthroscopy. Outcomes following superior labral anterior-posterior (SLAP) repairs in young athletes have been well documented. Superior labral repairs in older patient population continue to remain controversial due to concerns of postoperative complications including persistent preoperative symptoms, pain, stiffness, and higher rates of revision surgery. Indications: We present a case of a highly active 38-year-old woman who failed 1½ years of nonoperative management of a type IIB SLAP tear with extension to the posterior labrum. Her symptoms continued to limit her hobbies and work. Technique: A knotless single-anchor SLAP repair was performed along with debridement of the posterior frayed labrum. No biceps tenotomy or tenodesis was performed after full evaluation of the tendon failed to demonstrate evidence of synovitis, tendinopathy, or tear. The patient also did not have any concomitant shoulder pathology, including a rotator cuff tear or chondral lesion. Results: At 6 months, the patient had regained full range of motion similar to the contralateral side. She had returned to her normal activities and sports, including tennis. Discussion/Conclusion: Successful outcomes following SLAP repairs in patients over 35 years can be achieved, but treatment should be individualized with particular attention to concomitant pathology involving the rotator cuff, chondral surface, or biceps tendon which may require tenodesis or tenotomy.